Method and apparatus for producing membrane-electrode assembly

By combining the liquid imparting process and the hot pressing process in the manufacturing process of the film and electrode joint, the problems of insufficient adhesion and low productivity of the electrolyte membrane and the catalyst layer in the prior art are solved, and high efficiency and low cost are achieved film and electrode joint manufacture.

CN114788057BActive Publication Date: 2025-02-14TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080085975.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-12-21
Publication Date
2025-02-14
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

When manufacturing the film and electrode joint of solid polymer fuel cells, it is difficult for the prior art to achieve good adhesion between the electrolyte membrane and the catalyst layer under the condition of easing the thermal crimping, and the productivity is low and the cost is high.

Method used

The liquid imparting step is used to impart liquid to the surface of the catalyst layer before bonding under an atmospheric atmosphere, and the gas diffusion layer with the catalyst layer is bonded with the electrolyte film by hot pressing step.

Benefits of technology

Under the condition of ease of hot pressing, the adhesion between the electrolyte membrane and the catalyst layer is improved, productivity is improved, and manufacturing costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114788057B_ABST
    Figure CN114788057B_ABST
Patent Text Reader

Abstract

A method for manufacturing a membrane-electrode assembly, wherein a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane, the method comprising: a liquid imparting step of imparting liquid only to the surface of the catalyst layer before bonding in an atmospheric atmosphere; and a thermocompression bonding step of bonding the gas diffusion layer with the catalyst layer to which the liquid has been imparted to the electrolyte membrane by thermocompression bonding. A method for manufacturing a membrane-electrode assembly in which a polymer electrolyte membrane is bonded to a gas diffusion layer with a catalyst layer, wherein the method can simultaneously achieve relaxation of thermocompression bonding conditions and improvement of the adhesion between the gas diffusion layer with a catalyst layer and the electrolyte membrane with high productivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method and apparatus for manufacturing a "membrane-electrode assembly", wherein the membrane-electrode assembly is a component formed by joining a polymer electrolyte membrane and a catalyst layer, which is used in electrochemical devices such as solid polymer fuel cells, i.e., an embodiment of a membrane-catalyst assembly. Background Art

[0002] Fuel cells are power generation devices that generate electricity by electrochemically oxidizing fuels such as hydrogen and methanol, and have attracted attention as a clean energy supply source in recent years. Among them, the standard operating temperature of solid polymer fuel cells is as low as about 100°C, and the energy density is high, so it is expected to be widely used as a power generation device for smaller-scale distributed power generation facilities and mobile objects such as automobiles or ships. Polymer electrolyte membranes (hereinafter sometimes referred to as "electrolyte membranes") are key materials for solid polymer fuel cells. In recent years, further research has been conducted on their application to hydrogen infrastructure-related equipment such as solid polymer electrolyte membrane water electrolysis devices and electrochemical hydrogen pumps.

[0003] When a polymer electrolyte membrane is applied to such an electrochemical device, a component formed by bonding an electrolyte membrane and a catalyst layer is used. An example of such a component is a membrane-electrode assembly (MEA) in which a gas diffusion layer with a catalyst layer is formed on the surface of an electrolyte membrane.

[0004] As a method for manufacturing MEA, the following method is known. First, a sheet called a gas diffusion layer formed of gas-permeable carbon paper or the like is used as a substrate, and a catalyst solution is applied to the surface of the sheet. Then, the solvent in the applied catalyst solution is evaporated to form a dry gas diffusion layer with a catalyst layer. Furthermore, the dry gas diffusion layer with a catalyst layer is thermally pressed with an electrolyte membrane using a surface press or a roller press to join the gas diffusion layer with the catalyst layer to the polymer electrolyte membrane. The reason for adopting the method of joining the catalyst layer to the electrolyte membrane after the catalyst layer is dried as described above is that if the solvent in the catalyst solution adheres to the electrolyte membrane, the electrolyte membrane will swell and wrinkle, and the shape will be distorted.

[0005] However, when the gas diffusion layer with a catalyst layer in a dry state is hot-pressed to the electrolyte membrane, if the pressurization is not carried out for a long time at high temperature and high pressure, the adhesion between the catalyst layer and the electrolyte membrane may be insufficient. On the other hand, if strict hot-pressing conditions are applied to improve the adhesion between the catalyst layer and the electrolyte membrane, the gas diffusion may be reduced due to the compression deformation of the catalyst layer, making it difficult to obtain good power generation performance, or the thermal stress may damage the electrolyte membrane and reduce the durability, and further, the gas diffusion may be reduced or damaged due to the compression deformation of the gas diffusion layer. On the other hand, in order to reduce the damage to the gas diffusion layer with a catalyst layer and the electrolyte membrane, simply reducing the temperature and pressure of the pressurization requires a corresponding extension of the pressurization time, so the productivity is greatly reduced.

[0006] Therefore, various techniques have been proposed to achieve good adhesion between the electrolyte membrane and the catalyst layer while relaxing the thermocompression bonding conditions.

[0007] Prior art literature

[0008] Patent Literature

[0009] For example, the following methods have been proposed: as in Patent Document 1, a method in which a catalyst solution is semi-dried and the catalyst layer is bonded to an electrolyte membrane while a slight amount of solvent components remain in the catalyst layer; as in Patent Document 2, a solution containing a proton-conductive binder resin is coated on the surface of the dried catalyst layer and the catalyst layer is bonded to the electrolyte membrane before the solution is completely dried; as in Patent Document 3, a method in which a stacked body including an electrolyte membrane and a catalyst layer is crimped while being immersed in a liquid.

[0010] Patent Document 1: Japanese Patent No. 4240272

[0011] Patent Document 2: Japanese Patent Application Publication No. 2013-69535

[0012] Patent Document 3: Japanese Patent Application Publication No. 2009-140652 Summary of the invention

[0013] Problems to be solved by the invention

[0014] According to the method described in Patent Document 1, by leaving the catalyst layer with a solvent component that can only soften the bonding surface of the electrolyte membrane with the catalyst layer, the electrolyte membrane and the catalyst layer can be made to have good adhesion under the conditions of relaxed thermal compression bonding without causing wrinkles to the electrolyte membrane. However, while the solvent in the catalyst solution is partially removed by heating, it is difficult to dry and control the solvent residue to be in the same state on the entire surface of the catalyst layer. The interface resistance between the electrolyte membrane and the catalyst layer caused by the difference in the drying state within the catalyst layer is large, and wrinkles are generated by the deformation of the electrolyte membrane, and cracks are generated on the surface of the catalyst layer. There is a problem of unstable quality. In addition, there is also a narrow range of solvent residues, which leads to problems such as rising costs caused by reduced productivity. Further, since the solvent composition of the catalyst solution is limited, it is difficult to flexibly respond to changes in the variety of the catalyst layer.

[0015] In addition, according to the method described in Patent Document 2, a solution of a proton-conductive binder resin is applied to the bonding surface of the catalyst layer and the electrolyte membrane, and the bonding is performed before the solution is completely dried, so that the solution acts as an adhesive, and the adhesion between the electrolyte membrane and the catalyst layer can be good even at low temperature and low pressure. However, since the solution of a proton-conductive binder resin is used to bond the electrolyte membrane and the catalyst layer, the manufacturing cost increases. In addition, there are the following problems: the binder resin is the same component as the electrolyte membrane, and the membrane thickness of the electrolyte membrane is substantially increased, thereby increasing the resistance. In addition, since the organic solvent in the solution remains at the interface between the electrolyte membrane and the catalyst layer, it may cause a decrease in power generation performance.

[0016] In addition, according to the method described in Patent Document 3, by a crimping process in which the body to be joined including the electrolyte membrane and the body to be joined including the catalyst layer are crimped while being immersed in a liquid, the electrolyte in the electrolyte membrane and the catalyst layer fully absorbs the liquid, and is pressurized in a softened state, so that it enters the concave and convex parts of the bonding surface of the catalyst layer and the gas diffusion layer as the bonding object to obtain strong bonding, and the bonding between the layers constituting the membrane-electrode assembly can be improved without increasing the temperature and pressure during pressurization. However, since the components other than the interface related to the bonding are immersed in the liquid as a whole, it is difficult to suppress the swelling of the electrolyte membrane and maintain the shape. Furthermore, since the deformation behavior of each component caused by drying after crimping is different, it is difficult to obtain a uniform and flat joint body, and there is also a problem that it is difficult to improve productivity by continuous processing using a rolled long strip component.

[0017] The object of the present invention is to provide the following manufacturing method, which can achieve the relaxation of hot pressing conditions (pressing pressure, pressing temperature, pressing time) and the improvement of the tightness between the gas diffusion layer with a catalyst layer and the electrolyte membrane at the same time with high productivity when manufacturing a component formed by joining a polymer electrolyte membrane and a gas diffusion layer with a catalyst layer (hereinafter referred to as a "membrane-electrode assembly").

[0018] Means for solving problems

[0019] In order to solve the above-mentioned problems, the manufacturing method of the membrane-electrode assembly of the present invention has the following structure. That is, the manufacturing method of the membrane-electrode assembly, the membrane-electrode assembly is formed by bonding a gas diffusion layer with a catalyst layer to an electrolyte membrane, the manufacturing method comprising: a liquid imparting step, in an atmospheric atmosphere, imparting liquid only to the surface of the catalyst layer before bonding; and a thermocompression bonding step, bonding the gas diffusion layer with the catalyst layer to which the liquid has been imparted to the electrolyte membrane by thermocompression bonding.

[0020] In addition, the manufacturing device of the membrane-electrode assembly of the present invention has the following configuration. That is, the manufacturing device of the membrane-electrode assembly, the membrane-electrode assembly is formed by bonding a gas diffusion layer with a catalyst layer to an electrolyte membrane, the manufacturing device having: a liquid imparting mechanism that imparts liquid to the surface of the catalyst layer before bonding; and a thermocompression bonding mechanism that uses thermocompression bonding to bond the gas diffusion layer with the catalyst layer to which the liquid has been imparted to the electrolyte membrane.

[0021] In the method for producing a membrane / electrode assembly of the present invention, the liquid applied in the liquid applying step is preferably a liquid containing water.

[0022] In the method for producing a membrane / electrode assembly of the present invention, it is preferred that the content of water in the liquid containing water is 90% by mass or more and 100% by mass or less.

[0023] In the method for producing a membrane / electrode assembly of the present invention, it is preferred that the liquid applied in the liquid applying step is pure water.

[0024] In the method for producing a membrane / electrode assembly of the present invention, it is preferred that in the liquid applying step, the liquid is applied in the form of droplets to the catalyst layer surface of the gas diffusion layer with the catalyst layer.

[0025] In the method for producing a membrane / electrode assembly of the present invention, it is preferred that in the liquid applying step, the liquid is applied using a sprayer.

[0026] In the method for producing a membrane-electrode assembly of the present invention, it is preferred that in the liquid applying step, the amount of the liquid in the thermocompression bonding step is2 The surface of the catalyst layer is not less than 0.1 μL and not more than 5 μL.

[0027] In the method for producing a membrane-electrode assembly of the present invention, it is preferable to use a hydrocarbon-based electrolyte membrane as the electrolyte membrane.

[0028] The method for producing a membrane-electrode assembly of the present invention preferably includes joining a gas diffusion layer with a catalyst layer to the surface of the electrolyte membrane by any of the above-mentioned methods.

[0029] The method for manufacturing the membrane-electrode assembly of the present invention preferably includes the following steps: a step of applying a catalyst solution on one side of an electrolyte membrane and drying it to form a first catalyst layer; and a step of joining a gas diffusion layer with a catalyst layer to the other side of the electrolyte membrane using any of the above methods to form a second catalyst layer.

[0030] The method for producing a membrane-electrode assembly of the present invention preferably further comprises a step of covering the first catalyst layer with a covering film, and the step of forming the second catalyst layer is performed in a state where the first catalyst layer is covered with the covering film.

[0031] The method for manufacturing the membrane-electrode assembly of the present invention preferably includes the following steps: a step of applying a catalyst solution on one side of an electrolyte membrane to form a first catalyst layer; a step of covering the first catalyst layer with a gas diffusion layer before drying; a step of drying the catalyst layer through the gas diffusion layer; and a step of forming a second catalyst layer by joining a gas diffusion layer with a catalyst layer to the other side of the electrolyte membrane using any of the methods described in the above items.

[0032] In the membrane / electrode assembly manufacturing apparatus of the present invention, it is preferable that the liquid applying mechanism is a mechanism for applying the liquid in the form of droplets to the surface of the catalyst layer.

[0033] In the membrane / electrode assembly manufacturing apparatus of the present invention, it is preferable that the liquid applying mechanism is a sprayer.

[0034] Effects of the Invention

[0035] According to the present invention, a membrane-electrode assembly can be produced with high productivity while achieving both relaxation of thermocompression bonding conditions (pressing pressure, pressing temperature, pressing time) and improvement of adhesion between a gas diffusion layer with a catalyst layer and an electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] [ Figure 1 ] is a side view showing the schematic structure of the first embodiment of the membrane-electrode assembly manufacturing apparatus of the present invention.

[0037] [ Figure 2 ] is a side view showing a schematic structure for forming a first catalyst layer in a second embodiment of the membrane / electrode assembly manufacturing apparatus of the present invention.

[0038] [ Figure 3 ] is a side view showing a schematic structure for forming a second catalyst layer in a second embodiment of the membrane-electrode assembly manufacturing apparatus of the present invention.

[0039] [ Figure 4 ] is a side view showing a schematic structure for forming a first catalyst layer in a third embodiment of the membrane / electrode assembly manufacturing apparatus of the present invention.

[0040] [ Figure 5 ] is a side view showing a schematic structure for forming a second catalyst layer in the third embodiment of the membrane / electrode assembly manufacturing apparatus of the present invention.

[0041] [ Figure 6 ] is a side view showing the schematic structure of a heat insulating plate in the first embodiment of the membrane-electrode assembly manufacturing apparatus of the present invention. DETAILED DESCRIPTION

[0042] Although the present invention is not limited at all, the effect of the present invention can be considered as follows. In the hot pressing process, the electrolyte membrane and the gas diffusion layer with the catalyst layer are clamped and pressed while the liquid is applied to the joint surface of the gas diffusion layer with the catalyst layer and the electrolyte membrane, so that the air present at the interface is driven out and the state in which almost only the liquid exists between the electrolyte membrane and the gas diffusion layer with the catalyst layer is changed. By further applying heat in this state, the liquid evaporates and the interface is vacuumized, so the adhesion between the gas diffusion layer with the catalyst layer and the electrolyte membrane is improved. Furthermore, the electrolyte membrane softens by contact with the liquid, so the adhesion between the two is further improved. It should be noted that the electrolyte membrane is maintained by clamping during hot pressing during contact with the liquid, so that the occurrence of swelling can be prevented. In addition, the liquid evaporated at the interface passes through the pores of the gas diffusion layer with the catalyst layer having a porous structure and is discharged to the outside of the membrane-electrode assembly.

[0043] It should be noted that the so-called "membrane-electrode assembly" in this specification refers to a component obtained by bonding a gas diffusion layer with a catalyst layer (so-called gas diffusion electrode) formed on one side of a substrate (gas diffusion layer) formed of gas-permeable carbon paper, etc., to an electrolyte membrane. In addition, since the focus is on the bonding surface between the electrolyte membrane and the catalyst layer, it is included in the technical field of "membrane-catalyst assembly".

[0044] In addition, the operation of further bonding a gas diffusion layer with a catalyst layer to the other side of an electrolyte membrane having a catalyst layer formed thereon, and the operation of bonding a gas diffusion layer with a catalyst layer to one side of an electrolyte membrane and then forming a catalyst layer on the other side are also included in the "manufacturing of a membrane-electrode assembly". As a method of forming a catalyst layer on one side or the other side of the electrolyte membrane, for example, a method of directly coating the catalyst layer or a method of transferring the catalyst layer using a catalyst layer transfer sheet can be used.

[0045] 〔Electrolyte membrane〕

[0046] The electrolyte membrane used in the method and apparatus for manufacturing the membrane-electrode assembly of the present invention is not particularly limited as long as it has proton conductivity and works as an electrolyte membrane used in a solid polymer fuel cell, a solid polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, etc., and known or commercially available substances can be used. As such an electrolyte membrane, a polymer electrolyte membrane is preferred, and for example, a fluorine-based electrolyte membrane formed by perfluorosulfonic acid or a hydrocarbon-based electrolyte membrane formed by a hydrocarbon-based polymer having proton conductivity imparted to a hydrocarbon-based skeleton can also be used.

[0047] In particular, hydrocarbon-based electrolyte membranes have higher glass transition temperatures and larger shrinkage deformations when heated than fluorine-based electrolyte membranes. Therefore, it is often difficult to find transfer conditions with excellent productivity using conventional heat pressing methods. However, the manufacturing method and manufacturing apparatus of the present invention can be appropriately applied.

[0048] As the electrolyte membrane, a composite electrolyte membrane in which a polymer electrolyte and a porous substrate are composited can be used.

[0049] 〔Composite electrolyte membrane〕

[0050] The composite electrolyte membrane is a membrane obtained by compounding a polymer electrolyte with a porous substrate, for example, by filling (impregnating) a polymer electrolyte into a porous substrate. As the porous substrate, for example, a hydrocarbon porous substrate with a hydrocarbon polymer compound as the main component, a fluorine porous substrate with a fluorine polymer compound as the main component, etc. can be cited.

[0051] Examples of hydrocarbon polymer compounds include polyethylene (PE), polypropylene (PP), polystyrene (PS), polyacrylate, polymethacrylate, polyvinyl chloride (PVC), polyvinylidene chloride (PVdC), polyester, polycarbonate (PC), polysulfone (PSU), polyethersulfone (PES), polyphenylene ether (PPO), polyarylene ether polymers, polyphenylene sulfide (PPS), polyphenylene sulfide sulfone, polyparaphenylene (PPP), polyarylene polymers, polyarylene ketone, polyether ketone (PEK), polyarylene phosphine oxide, polyether phosphine oxide, polybenzoxazole (PBO), polybenzothiazole (PBT), polybenzimidazole (PBI), polyamide (PA), polyimide (PI), polyetherimide (PEI), polyimide sulfone (PIS), and the like.

[0052] Examples of fluorine-based polymer compounds include polytetrafluoroethylene (PTFE), polyhexafluoropropylene, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVdF), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy fluororesin (PFA), and ethylene-chlorotrifluoroethylene copolymer (ECTFE).

[0053] From the viewpoint of water resistance, chemical resistance and mechanical properties, PE, PP, PPS, PEK, PBI, PTFE, polyhexafluoropropylene, FEP and PFA are preferred. From the viewpoint of chemical resistance and chemical durability, PTFE, polyhexafluoropropylene, FEP and PFA are more preferred. PTFE is particularly preferred because it has higher mechanical strength in molecular orientation.

[0054] As a composite electrolyte membrane, a membrane obtained by combining a hydrocarbon electrolyte with a fluorine-based porous substrate is particularly preferred. In this case, when combining, by adding a nonionic fluorine-based surfactant to the hydrocarbon electrolyte solution, it is easy to fill (impregnate) the hydrocarbon electrolyte in the fluorine-based porous substrate without gaps and efficiently.

[0055] The composite electrolyte membrane can be produced, for example, by impregnating a porous substrate with a polymer electrolyte solution and then drying to remove the solvent contained in the polymer electrolyte solution. Examples of the impregnation method include the following methods.

[0056] (1) A method of controlling the film thickness by lifting a porous substrate immersed in a polymer electrolyte solution and removing the excess solution;

[0057] (2) A method of applying a polymer electrolyte solution to a porous substrate by casting;

[0058] (3) A method of laminating a porous substrate onto a polymer electrolyte solution cast on a supporting substrate to impregnate the porous substrate.

[0059] 〔Catalyst layer〕

[0060] The catalyst layer used in the method and device for manufacturing the membrane-electrode assembly of the present invention is not particularly limited as long as it works as a catalyst layer used in a solid polymer fuel cell, a solid polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, etc. Generally, a catalyst layer having a porous structure formed by conductive particles such as carbon particles, catalyst particles such as platinum particles or platinum alloy particles supported on conductive particles, and electrolyte components such as ionomers having proton conductivity can be used.

[0061] As an example, conductive particles preferably include carbon such as oil furnace black, gas furnace black, acetylene black, thermal black, graphite, carbon nanotubes, graphene, and metal oxides such as tin oxide and titanium oxide. Catalyst particles preferably include single noble metals such as platinum, iridium, ruthenium, rhodium, and palladium, or alloys of manganese, iron, cobalt, nickel, copper, zinc, and platinum, or ternary alloys of platinum and ruthenium, and iridium oxide. In addition, as electrolyte components, it is preferred to use perfluorocarbon sulfonic acid polymers such as "Nafion" (registered trademark, manufactured by Chemours), "Aquivion" (registered trademark, manufactured by Solvay), "Flemion" (registered trademark, manufactured by Asahi Glass Co., Ltd.), "Aciplex" (registered trademark, manufactured by Asahi Kasei Corporation), and "Fumion" F (registered trademark, manufactured by FuMA-Tech) and other hydrocarbon polymers such as polysulfone sulfonic acid, polyaryletherketonesulfonic acid, polybenzimidazolylsulfonic acid, polybenzimidazolylsulfonic acid, polystyrenesulfonic acid, polyetheretherketonesulfonic acid, and polyphenylsulfonic acid.

[0062] The catalyst solution is not particularly limited as long as the catalyst layer materials are dispersed in a solvent that can be evaporated by drying and is sufficient to form a catalyst layer on the electrolyte membrane. Generally speaking, water, methanol, ethanol, 1-propanol, 2-propanol, tert-butyl alcohol, alcohols such as ethylene glycol, N,N-dimethylformamide, N-methyl-2-pyrrolidone, etc. can be preferably used as the solvent.

[0063] 〔Gas diffusion layer〕

[0064] For the gas diffusion layer of the manufacturing method and manufacturing apparatus of the membrane-electrode assembly of the present invention, it suffices that it functions as a gas diffusion layer used in a polymer electrolyte fuel cell, a polymer electrolyte membrane type water electrolysis apparatus, an electrochemical hydrogen pump, etc., and there is no particular limitation. Generally, a gas diffusion layer with low resistance, capable of current collection or power supply, and capable of forming a catalyst layer can be used. As the constituent material of the gas diffusion layer, for example, carbonaceous materials and conductive inorganic substances can be cited. For example, carbon materials such as a fired body from polyacrylonitrile, a fired body from pitch, graphite, and expanded graphite, stainless steel, molybdenum, titanium, etc. can be exemplified. Their forms are not particularly limited, and for example, they can be used in fibrous or particulate form. From the aspect of fuel permeability, fibrous conductive substances (conductive fibers) such as carbon fibers are preferred. As the gas diffusion layer using conductive fibers, any structure of woven fabric or non-woven fabric can also be used. As this woven fabric, plain weave fabric, twill weave fabric, satin weave fabric, figured weave fabric, pattern fabric (Japanese: 綴織), etc. can be used without particular limitation. In addition, as the non-woven fabric, non-woven fabrics obtained by a papermaking method, a needle punching method, a spunbond method, a water jet punch method, a meltblown method, etc. can be used without particular limitation. In addition, it can also be a knitted fabric. Among the above-mentioned fabrics, especially in the case of using carbon fibers, the following can be preferably used: a woven fabric obtained by carbonizing or graphitizing a plain weave fabric using flame-retardant spun yarn; a non-woven fabric obtained by carbonizing or graphitizing a non-woven fabric processed from flame-retardant yarn by a needle punching method, a water jet punch method, etc.; a non-woven fabric felt obtained by a papermaking method using flame-retardant yarn, carbonized yarn, or graphitized yarn. Especially from the aspect of obtaining a thin and strong fabric, non-woven fabric and fabric are preferred. As the carbon fibers used in this gas diffusion layer, polyacrylonitrile (PAN) - based carbon fibers, phenol - based carbon fibers, pitch - based carbon fibers, rayon - based carbon fibers, etc. can be cited. As such carbon fibers, for example, carbon paper TGP series manufactured by Toray Industries, Inc., SO series, carbon cloth manufactured by E-TEK, etc. can be used.

[0065] In addition, the following treatments can also be performed on the gas diffusion layer: a hydrophobic treatment for preventing a decrease in gas diffusion and permeability caused by water retention; a local hydrophobic and hydrophilic treatment for forming a water discharge path; an addition of carbon powder for reducing resistance; a platinum plating for imparting potential corrosion resistance, etc. In addition, a conductive intermediate layer containing at least an inorganic conductive substance and a hydrophobic polymer can also be provided between the electrode substrate and the catalyst layer. Especially when the electrode substrate is a carbon fiber woven fabric or non-woven fabric with a large porosity, by providing a conductive intermediate layer, a performance degradation caused by the infiltration of the catalyst solution into the gas diffusion layer can be suppressed.

[0066] [Gas Diffusion Layer with Catalyst Layer]

[0067] For the gas diffusion layer with a catalyst layer provided in the manufacturing method and manufacturing apparatus of the membrane-electrode assembly of the present invention, there is no limitation as long as the structure in which the catalyst layer is formed on the gas diffusion layer. Generally speaking, a layer obtained by directly applying the catalyst solution to the gas diffusion layer and drying it can be used. Alternatively, a layer obtained by once applying the catalyst solution to a temporary substrate different from the gas diffusion layer, drying it and forming it into a sheet, and then hot pressing it with the gas diffusion layer, and removing the temporary substrate can be used.

[0068] [Liquid application process]

[0069] The liquid imparting step is a step of imparting liquid to the catalyst layer surface of the gas diffusion layer with the catalyst layer before bonding, that is, the bonding surface with the electrolyte membrane. The so-called imparting of liquid refers to a state in which the liquid is attached to the catalyst layer surface of the gas diffusion layer with the catalyst layer in an exposed state. The liquid preferably does not substantially penetrate into the catalyst layer. If the liquid does not penetrate into the catalyst layer, the electrolyte components in the catalyst layer will not dissolve, the strength of the catalyst layer will not decrease, and the generation of cracks in the hot pressing process can be effectively prevented.

[0070] In the liquid application process, liquid is applied only to the surface of the catalyst layer under the atmosphere. By applying liquid only to the surface of the catalyst layer, the number of process control parameters is reduced compared to the case where liquid is applied to both the catalyst layer and the electrolyte membrane, and thus the following advantages are achieved: the manufacturing conditions are easily stabilized, and the amount of liquid applied to the bonding surface is easily controlled and managed; and the uneven amount of liquid in the bonding surface caused by contact between liquid droplets before the thermal compression bonding process can be suppressed.

[0071] In addition, by imparting liquid under the atmospheric atmosphere, it is possible to impart liquid only to the catalyst layer surface, and it is possible to suppress the penetration of liquid into the catalyst layer. By suppressing the penetration of liquid into the catalyst layer, it is possible to effectively suppress the strength reduction and crack generation of the catalyst layer. As far as the liquid that penetrates into the catalyst layer is concerned, it does not contribute to the improvement of the adhesion of the interface, but the energy consumption for evaporation increases, so from the aspect of manufacturing cost, it is also effective to suppress the penetration of liquid into the catalyst layer.

[0072] In the liquid imparting process, the liquid is not particularly limited as long as it is evaporated by heating in the hot pressing process as a subsequent process and is a material that is not toxic to the electrolyte membrane and the gas diffusion layer with the catalyst layer. For example, alcohols such as water, methanol, ethanol, 1-propanol, 2-propanol, tert-butyl alcohol, and their mixed solutions can be used, and it is desirable to use a liquid containing at least water. If the liquid undergoes a sharp temperature change during hot pressing, the electrolyte membrane sometimes produces wrinkles, but since water has a high boiling point and specific heat compared to the above-mentioned alcohols, the temperature rise during hot pressing is slow, so if it is a liquid containing water, their damage can be suppressed. In addition, compared with alcohol, water has low permeability to the catalyst layer, so it is possible to prevent the generation of cracks caused by liquid penetration into the catalyst layer. Further, by using a liquid containing water, the present invention can be implemented at low cost, and the environmental load on manufacturing can also be reduced. It should be noted that even if there is a liquid remaining in the membrane electrode assembly joined by the manufacturing method and manufacturing device of the present invention, if it is water, it will not affect the performance of the equipment using it. As the liquid containing water, the water content is more preferably 50 mass % to 100 mass %, further preferably 90 mass % to 100 mass %, and more preferably 100 mass %. That is, it is most preferred to use pure water as the liquid. Here, the so-called pure water is high-purity water that does not contain impurities, and refers to JIS K 0557 (1998) A4 grade water obtained by using a commercially available pure water production device collected from a reverse osmosis membrane and an ion exchange resin, or water of equivalent quality.

[0073] In addition, the solid component material may be contained in the liquid in a dissolved or dispersed state as long as the liquid has fluidity as a whole and the effects of the present invention can be obtained.

[0074] In the liquid imparting step, the method of imparting the liquid is not particularly limited, and examples include a method of forming a uniform coating film on the surface of the catalyst layer using a gravure coater, a die coater, a comma coater, etc., and a method of imparting the liquid to the surface of the catalyst layer in the form of droplets. The method of imparting the liquid to the surface of the catalyst layer in the form of droplets is particularly preferred. The so-called droplet here refers to the situation where countless droplets are attached to the surface of the catalyst layer. It should be noted that the so-called droplet refers to a liquid mass gathered together by surface tension, and its size is 1 cm on the catalyst layer. 2 If the liquid is applied in the form of droplets, a minimum amount of liquid required to soften the electrolyte membrane can be evenly applied to the bonding surface during bonding. It should be noted that the so-called uniform application of droplets means that the droplets are applied uniformly every 1 cm 2The total amount of liquid imparted to the bonding surface is the same at any position. In addition, even if it is a liquid that is easy to repel the catalyst layer and difficult to form a uniform coating film, it can be easily imparted if it is in the form of a droplet. Further, if it is in the form of a droplet, the contact area with the catalyst layer is small, so the penetration of the liquid into the catalyst layer until the thermal compression can be suppressed to a minimum. It should be noted that, with respect to the droplets, by the clamping in the thermal compression process, the droplets spread out at the interface and combine with the surrounding droplets, so that the electrolyte membrane can be softened on all sides of the interface.

[0075] In the liquid application step, it is preferred that the amount of liquid at the start of the thermal compression bonding step be 100% relative to 1 cm 2 The liquid is applied to the catalyst layer surface in a manner of not less than 0.1 μL and not more than 5 μL. When the amount of liquid in the hot pressing step is within the above-mentioned preferred range, the electrolyte membrane can be sufficiently softened and the adhesion is sufficient. There will be no situation where liquid droplets partially fail to combine during clamping in the hot pressing step to produce unsoftened parts of the electrolyte membrane. On the other hand, liquid dripping will not occur during transportation. Since almost all the liquid evaporates due to the heating during hot pressing, there will be no situation where the electrolyte membrane swells at the moment when the clamping is released due to the liquid remaining at the interface. Regarding the liquid amount, it is more preferably relative to every 1 cm 2 The surface of the catalyst layer is 0.1 μL or more and 0.8 μL or less. It should be noted that the liquid volume can be measured as follows: a sample sheet such as a PET film whose weight has been measured is affixed to the surface of the catalyst layer of the gas diffusion layer with the catalyst layer in a manner of stacking with the catalyst layer, and after the liquid is applied in the liquid application step, the sample sheet with the liquid is taken out in the hot pressing step just before the sample sheet and the electrolyte membrane are about to come into contact, and its weight is measured, and the weight difference is calculated per 1 cm 2 The size of the sample piece at this time can be a square with a side length of 1 cm to 10 cm.

[0076] In addition, the smaller the average diameter of the droplets, the more preferred. Specifically, it is preferably 300 μm or less when attached to the catalyst layer surface. The smaller the average diameter, the shorter the distance between the droplets can be, so that the droplets can be combined with a smaller amount of liquid during the clamping in the thermal compression bonding process.

[0077] In the liquid imparting step, the means for imparting the liquid in the form of droplets is not particularly limited, and a method of ejecting droplets by a sprayer or inkjet, a method of causing droplets to condense on the bonding surface in a humidified atmosphere, a method of ejecting a liquid atomized by an ultrasonic vibrator, etc., can be used. However, in terms of being able to efficiently impart the liquid while controlling the amount of liquid, a method of ejecting droplets by a sprayer is preferred. In addition, as a sprayer for ejecting droplets, there is no particular limitation, and a two-fluid spray nozzle that atomizes the liquid by compressed air and sprays it can be used.

[0078] When using the above-mentioned mechanism for applying liquid in the form of droplets, it is preferred to surround the liquid applying mechanism such as a spray nozzle with a chamber in order to suppress the droplets from scattering around. In addition, the chamber may not be depressurized, but it is preferred to suppress the droplets from scattering around the gap between the chamber and the catalyst layer by slightly reducing the pressure to a negative pressure relative to the atmospheric pressure.

[0079] [Thermocompression bonding process]

[0080] The gas diffusion layer with the catalyst layer that has undergone the liquid imparting step is then subjected to a heat pressing step of heat pressing the electrolyte membrane. The so-called heat pressing step refers to a step of heating and pressing the gas diffusion layer with the catalyst layer and the electrolyte membrane in a stacked state where the liquid imparted surface of the gas diffusion layer with the catalyst layer is in contact with the electrolyte membrane, thereby bonding them.

[0081] In the thermal compression step, the time from when the gas diffusion layer with the catalyst layer contacts the electrolyte membrane until the clamping pressure acts on them is preferably 0.1 seconds or less. When this time is within the above preferred range, the possibility of swelling of the electrolyte membrane due to the adhesion of the liquid is low, and the adhesion of the liquid and the fixation of the electrolyte membrane by thermal compression bonding are carried out at about the same time, so that swelling can be suppressed.

[0082] The heating temperature in the thermocompression bonding process is not particularly limited, and is preferably above the boiling point of the liquid imparted to the gas diffusion layer with the catalyst layer (hereinafter referred to as the "liquid boiling point") and below 220°C. The so-called heating temperature refers to the highest temperature reached at the joint surface of the electrolyte membrane and the catalyst layer in the thermocompression bonding process, and a thermocouple can be used for the measurement. When the heating temperature is within the above-mentioned preferred range, the evaporation of the liquid does not take time and the productivity is excellent. On the other hand, the electrolyte membrane will not be damaged by heat. The heating temperature in the thermocompression bonding process is more preferably above the liquid boiling point and below 160°C. It should be noted that the so-called liquid boiling point is the boiling point when the external pressure is one atmosphere. When the evaporated liquid is a single composition, it refers to the boiling point of the liquid. In the case of a mixture, it refers to the value of the monomer with the highest boiling point as a monomer among the components of the mixture.

[0083] The pressure applied to the electrolyte membrane and the catalyst layer in the hot pressing process can be appropriately set, preferably 1 MPa or more and 20 MPa or less. In the case of the above preferred range, the electrolyte membrane can be fully fitted with the gas diffusion layer with the catalyst layer. On the other hand, since no excessive pressure is applied to the gas diffusion layer with the catalyst layer and the electrolyte membrane, the structure of the gas diffusion layer with the catalyst layer will not be destroyed, the mechanical damage to the electrolyte membrane will not increase, and the durability and power generation performance will not decrease. The pressure in the hot pressing process is more preferably 1 MPa to 10 MPa.

[0084] The clamping form in the hot pressing process is not particularly limited, and can be a line contact form in which the electrolyte membrane and the gas diffusion layer with the catalyst layer are in single linear contact such as a hot pressing roller, or a surface contact form in which the electrolyte membrane and the gas diffusion layer with the catalyst layer are in surface contact with a width along the conveying direction such as a double-belt press mechanism.

[0085] [Manufacturing method based on roll-to-roll method]

[0086] The method for producing the membrane-electrode assembly of the present invention is preferably carried out in a roll-to-roll process, that is, a process in which the liquid application step and the thermocompression bonding step are continuously carried out in a roll-to-roll process.

[0087] The roll-to-roll manufacturing method is, for example, the following manufacturing method: a long roll of electrolyte membrane and a long roll of gas diffusion layer with a catalyst layer are respectively continuously unwound and conveyed, a liquid application process and a heating and pressing process are performed to obtain a membrane-electrode assembly, and the obtained membrane-electrode assembly is wound into a roll.

[0088] The membrane-electrode assembly production apparatus described below is an example of a production apparatus capable of implementing a roll-to-roll production method.

[0089] It should be noted that the above is a description of the production method of the present invention, but it can be easily understood from the above description and the following description of the embodiment that this specification also discloses the following production apparatus for implementing the production method.

[0090] (1) A manufacturing device for a membrane-electrode assembly, wherein a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane, the manufacturing device comprising: a liquid imparting mechanism for imparting liquid to a surface of the catalyst layer before bonding; and a thermocompression bonding mechanism for bonding the gas diffusion layer with the catalyst layer to which the liquid has been imparted to the electrolyte membrane by thermocompression bonding;

[0091] (2) The membrane-electrode assembly manufacturing apparatus according to (1), wherein the liquid applying mechanism is a mechanism for applying the liquid in the form of droplets to the surface of the catalyst layer;

[0092] (3) The membrane / electrode assembly manufacturing apparatus according to (2), wherein the liquid applying mechanism is a sprayer.

[0093] Hereinafter, the specific implementation mode of the present invention will be described with reference to the schematic diagram of the manufacturing device for implementing the manufacturing method of the present invention. It should be noted that the following description is recorded to facilitate the understanding of the present invention and does not limit the present invention in any way, but it is easy for those skilled in the art to understand that the reference to the preferred mode and the variation of the mode in each embodiment can be simultaneously interpreted as a description of the manufacturing method or manufacturing device of the present invention as a superordinate concept. It should be noted that in this specification, for convenience, the top of each figure is described as "top" and the bottom is described as "bottom", but the up and down direction of each figure is not necessarily limited to the vertical direction relative to the ground.

[0094] [First Embodiment: Production of Membrane-Electrode Assembly 1]

[0095] Figure 1 It is a side view showing a schematic structure of the membrane-electrode assembly production apparatus of the present invention.

[0096] In the membrane / electrode assembly manufacturing apparatus 100 according to the present embodiment, the membrane / electrode assembly is manufactured as follows.

[0097] The electrolyte membrane 10 is unwound from the electrolyte membrane supply roll 11 and supplied to the hot pressing section P through the guide roll 12. Gas diffusion layer supply rolls 21A and 21B with catalyst layers are provided above and below the unwound electrolyte membrane 10, respectively. The gas diffusion layer with catalyst layer bonded to the upper surface of the electrolyte membrane 10 is formed using the gas diffusion layer 20A with catalyst layer. The gas diffusion layer 20A with catalyst layer is made by applying a catalyst solution on the gas diffusion layer in advance, for example, and is unwound from the gas diffusion layer supply roll 21A with catalyst layer, and is conveyed while carrying the gas diffusion layer side opposite to the catalyst layer forming surface in the order of the support roll 31A and the guide roll 22A. The gas diffusion layer 20B with catalyst layer for forming the gas diffusion layer with catalyst layer formed on the lower surface of the electrolyte membrane 10 is unwound from the gas diffusion layer supply roll 21B with catalyst layer, and is conveyed while carrying the gas diffusion layer side in the order of the support roll 31B and the guide roll 22B. In this manner, the gas diffusion layers 20A and 20B with catalyst layers are supplied to the thermal compression bonding portion P so that the surfaces on which the catalyst layers are formed face the electrolyte membrane 10 .

[0098] It should be noted that the gas diffusion layer has air permeability. The so-called air permeability means that it has a property that allows gas to pass through, and examples thereof include the case where it has pores that are connected in the thickness direction. By having air permeability, the vapor of the liquid generated during the thermal compression bonding can be effectively discharged.

[0099] In order to remove wrinkles and slack from the electrolyte membrane 10 and the gas diffusion layers with catalyst layers 20A and 21B supplied to the thermal compression bonding section P, it is preferable to use tenter rolls as the guide rolls 12 and 22A and 22B.

[0100] It should be noted that in the membrane-electrode assembly manufacturing device 100 involved in this embodiment, a gas diffusion layer with a catalyst layer is bonded to both surfaces of the electrolyte membrane 10, but it can also be configured so that a gas diffusion layer with a catalyst layer is bonded to only one surface of the electrolyte membrane 10.

[0101] By bonding a gas diffusion layer with a catalyst layer to only one side of the electrolyte membrane, it is possible to provide functions by clamping a membrane hollowed out into a frame shape before further bonding a gas diffusion layer with a catalyst layer to the other side of the electrolyte membrane. Alternatively, the electrolyte membrane is cut into a desired size in a state where a gas diffusion layer with a catalyst layer is bonded to only one side, and then bonded to a frame-shaped membrane material and a gas diffusion layer with a catalyst layer, thereby making a single MEA.

[0102] In this embodiment, the spray nozzle 30A is disposed so as to face the gas diffusion layer 20A with a catalyst layer supported on the support roller 31A. The spray nozzle 30A has a spray port facing the central axis of the support roller 31A and is disposed at a position spaced a predetermined distance from the support roller 31A. It should be noted that, depending on the substrate width of the gas diffusion layer 20A with a catalyst layer, one or more spray nozzles 30A are disposed in the width direction of the gas diffusion layer 20A with a catalyst layer.

[0103] The spray nozzle 30A is supplied with water from a water supply tank (not shown), and sprays the supplied water from a spray port to provide droplets to the bonding surface of the gas diffusion layer with the catalyst layer and the electrolyte membrane.

[0104] Furthermore, the spray nozzle 30A and the space S for the droplets to fly from the spray port of the spray nozzle 30A to the gas diffusion layer with a catalyst layer are surrounded by the nozzle chamber 32A, and the decompression tank 34A for decompressing the space S is connected to the nozzle chamber 32A by piping via a valve 33A for switching the decompression. The decompression tank 34A makes the space S negative pressure relative to the ambient pressure of the manufacturing device, so that the outside air is slightly sucked from the gap between the nozzle chamber 32A and the gas diffusion layer 20A with a catalyst layer to prevent the excess droplets from the spray nozzle 30A from flying around. It should be noted that the water accumulated in the nozzle chamber 32A is discharged from the discharge pipe (not shown) provided in the nozzle chamber 32A, and is returned to the water supply tank for reuse.

[0105] It should be noted that the above is a description of the liquid imparting mechanism for the gas diffusion layer 20A with a catalyst layer, but since the liquid imparting mechanism (spray nozzle 30B, nozzle chamber 32B, valve 33B, pressure reducing tank 34B) provided for the gas diffusion layer 20B with a catalyst layer is also of the same structure, the description is omitted.

[0106] The nozzle chambers 32A and 32B do not need to be depressurized, but a slight depressurization is preferred because it can prevent the droplets from scattering around. In this case, if the depressurization is too large, the amount of external gas sucked into the nozzle chambers 32A and 32B increases, which may disturb the airflow in the nozzle chambers 32A and 32B, and the accuracy of droplet delivery may decrease. Therefore, the depressurization degree of the nozzle chambers 32A and 32B is suitable within the range of -50.0 kPa, preferably within the range of -10.0 kPa, and more preferably within the range of -5.0 kPa relative to the ambient pressure (atmospheric pressure) of the manufacturing device.

[0107] In this way, the electrolyte membrane 10 and the gas diffusion layers 20A and 20B with catalyst layers to which the liquid is applied on the bonding surface with the electrolyte membrane 10 are supplied to the hot pressing section P and pass between the hot pressing rollers 40A and 40B. Figure 6 As shown in the figure, heat insulation plates 41A and 41B are respectively provided between the gas diffusion layer 20A with a catalyst layer and the hot press roll 40A, and between the gas diffusion layer 20B with a catalyst layer and the hot press roll 40B. By providing the heat insulation plates 41A and 41B, it is possible to prevent the liquid applied to the gas diffusion layers 20A and 20B with a catalyst layer from evaporating before hot pressing due to the radiant heat radiated from the hot press rolls 40A and 40B.

[0108] The hot pressing rollers 40A and 40B are connected to a driving mechanism not shown in the figure, and can rotate while controlling the speed. The hot pressing rollers 40A and 40B rotate at a constant speed while applying heat and pressure to the electrolyte membrane 10 and the gas diffusion layers 20A and 20B with catalyst layers, so that the electrolyte membrane 10 and the gas diffusion layers 20A and 20B with catalyst layers are transported synchronously, and the gas diffusion layers with catalyst layers are hot-pressed to both sides of the electrolyte membrane 10 to form a membrane-electrode assembly 13a. It should be noted that the illustration of the heating device, the pressurizing device, etc. is omitted for the hot roller press machines 40A and 40B.

[0109] The material of the hot press rollers 40A and 40B is not particularly limited, but preferably one roller is made of metal such as stainless steel, and the other roller is covered with an elastic body such as a resin or an elastomer material represented by rubber on the surface. By making one of the hot press rollers 40A and 40B of metal, the electrolyte membrane and the gas diffusion layer with a catalyst layer can be fully heated, and by making the surface layer of the other press roller of an elastic body, the press roller can flexibly deform with respect to the gas diffusion layer 20A and 20B with a catalyst layer, maintaining good line contact, thereby making the line pressure in the width direction of the substrate uniform.

[0110] As the material of the elastomer, for example, in the case of using rubber, fluororubber, silicone rubber, EPDM (ethylene propylene diene rubber), chloroprene rubber, CSM (chlorosulfonated polyethylene rubber), polyurethane rubber, NBR (nitrile rubber), hard rubber, etc. can be used. In addition, the rubber hardness of the elastomer is preferably in the range of 70 to 97° in Shore A standard. When the rubber hardness of the elastomer is within the above-mentioned preferred range, the deformation amount of the elastomer is moderate, and the clamping contact width with the gas diffusion layer 20A and 20B with the catalyst layer will not become too large, and the pressure required for the bonding of the electrolyte membrane 10 and the catalyst layer can be ensured. On the other hand, the clamping contact width will not become too small, and the clamping time required for bonding can be ensured.

[0111] As the heating mechanism of the heat press rollers 40A and 40B, various heaters, steam, heat media such as oil, etc. can be used, but there is no particular limitation. In addition, the heating temperature can be the same temperature or different temperatures for the upper roller and the lower roller.

[0112] There is no particular limitation on the method for controlling the clamping pressure in the hot pressing rollers 40A and 40B. The clamping pressure can be controlled using a pressurizing mechanism such as a hydraulic cylinder, or by setting a certain gap between the hot pressing rollers 40A and 40B through position control using a servo motor, etc., and controlling the clamping pressure by the size of the gap.

[0113] It should be noted that, in the present embodiment, although the hot pressing rollers 40A and 40B as a line contact mechanism are used in the hot pressing portion P, it is not limited to this. It may be a mechanism that uses multiple rollers to clamp the electrolyte membrane 10 and the gas diffusion layer with a catalyst layer 20A and 20B in multiple line contacts, or it may be a double belt press mechanism that clamps by surface contact. When multiple sets of rollers are used, the number of rollers set is not particularly limited, and is preferably 2 to 10 sets.

[0114] In this manner, the gas diffusion layers with catalyst layers are bonded to both surfaces of the electrolyte membrane 10 through the thermal compression bonding portion P, thereby forming a membrane-electrode assembly 13 a .

[0115] Note that the delivery roller 14 may be connected to a driving mechanism (not shown) and may convey the electrolyte membrane 10 by controlling the speed without the press rollers 40A and 40B pinching the electrolyte membrane 10 and the gas diffusion layers with catalyst layers 20A and 20B.

[0116] In addition, a heating mechanism (not shown) for heating the membrane-electrode assembly 13a obtained by bonding the catalyst layers to both sides of the electrolyte membrane by the thermal compression bonding section P may be provided. The heating mechanism may be provided, for example, between the thermal compression bonding section P and the delivery roller 14. As the heating mechanism, hot air or a heating roller may be used. The hot air temperature or the surface temperature of the heating roller is suitably 120°C to 250°C, and preferably 150°C to 230°C.

[0117] [Second Embodiment: Production of Membrane-Electrode Assembly 2]

[0118] In the second embodiment, firstly use Figure 2 The catalyst layer forming apparatus 101 shown forms a first catalyst layer on one surface of an electrolyte membrane. The first catalyst layer is formed as follows.

[0119] In the present embodiment, the electrolyte membrane 10' is supplied to the catalyst layer forming device 101 in a state supported by a support. The material of the support of the electrolyte membrane is not particularly limited, and for example, a PET film can be used.

[0120] The electrolyte membrane 10' with a support is unwound from the electrolyte membrane supply roller 11 and supplied to the catalyst solution coating mechanism 72 through the guide roller 12. The catalyst solution coating mechanism 72 is arranged opposite to the electrolyte membrane 10' carried by the support roller 73. The catalyst solution coating mechanism 72 uses a catalyst solution liquid delivery pump 71 to supply a catalyst solution from a catalyst solution tank 70, and forms a coating film by coating the supplied catalyst solution on the electrolyte membrane. The coating method of the catalyst solution in the catalyst solution coating mechanism 72 is not particularly limited. Methods such as a gravure coater, a die coater, a comma coater, a roll coater, a spray coater, and a screen printing method can be applied.

[0121] In addition, in the present embodiment, the catalyst layer is formed by applying the catalyst solution to the electrolyte membrane 10 ′, but the catalyst layer may be formed by transferring the catalyst layer to the electrolyte membrane 10 ′ using a catalyst layer transfer sheet.

[0122] Next, the coating film of the catalyst solution formed on the electrolyte membrane is dried by the drying mechanism 74, and the solvent in the catalyst solution is evaporated to form a dried first catalyst layer. The drying mechanism 74 does not particularly limit the method for drying the catalyst solution. A method of conveying a heat medium such as hot air, a heat oven method using a heat heater, etc. may be used.

[0123] The membrane / first catalyst layer assembly 16 in which the first catalyst layer is formed on the electrolyte membrane in this manner is fed out by the feed roll 14 , and is wound into a roll by the wind-up roll 17 while being attached to the support.

[0124] Next, use Figure 3 The membrane-electrode assembly manufacturing apparatus 102 according to the embodiment shown forms the second catalyst layer on the back side of the surface of the electrolyte membrane on which the first catalyst layer is formed. The second catalyst layer is formed as follows.

[0125] The membrane / first catalyst layer assembly 16 is unwound from the supply roll 18 , passes through the guide roll 12 , and further passes through the guide rolls 26A and 26B to peel the support 51 from the interface with the electrolyte membrane.

[0126] The membrane·first catalyst layer assembly 16 from which the support 51 is peeled off is laminated on the first catalyst layer surface by the cover film 61 unwound from the cover film supply roll 60 via the guide rolls 27A and 27B, and then supplied to the thermocompression bonding section P. It should be noted that the lamination of the cover film 61 may be performed before the support 51 is peeled off.

[0127] The covering film 61 is used to protect the first catalyst layer in the process of forming the second catalyst layer. As long as the function of the catalyst layer is not hindered by disassembly, the material is not particularly limited. Generally speaking, sheets of natural fibers represented by paper, etc., hydrocarbon plastic films represented by polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), polyimide, polyphenylene sulfide, etc., fluorine-based films represented by perfluoroalkoxyalkane (PFA), polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene copolymer (ETFE), etc., or materials that improve the adhesion to the adherend by giving acrylic adhesives, urethane acrylate adhesives, rubber adhesives, silicone adhesives, etc. to these materials. If it is a material that improves adhesion, the electrolyte membrane can be carried during the period when the electrolyte membrane is in contact with the liquid, so the effect of preventing the swelling of the electrolyte membrane can be further obtained.

[0128] The membrane·first catalyst layer assembly 16 supplied to the hot pressing section P undergoes the same liquid imparting process and hot pressing process as the first embodiment. While the first catalyst layer is covered with a covering membrane, the second catalyst layer is hot pressed as a gas diffusion layer with a catalyst layer to form a membrane·electrode assembly 13c.

[0129] The membrane·electrode assembly 13c that has passed through the hot pressing section P is wound into a roll by the winding roller 15. It should be noted that the covering film 61 can be wound in a state joined to the membrane·electrode assembly 13c, or it can be peeled off from the membrane·electrode assembly 13c in the hot pressing roller 40B immediately after pressurization. By winding the covering film 61 in a state joined to the membrane·electrode assembly 13c, it is possible to suppress the wrinkling and elongation of the electrolyte membrane with the catalyst layer and protect the catalyst layer from physical damage caused by external factors. In addition, by peeling off the covering film 61 immediately after the hot pressing, the catalyst layer is exposed, so that the vapor of the liquid generated in the hot pressing process can be effectively discharged. In this case, the catalyst layer can also be protected with a new covering film before winding.

[0130] In this state, there is no gas diffusion layer on the surface of the electrolyte membrane where the first catalyst layer is formed, but before further joining the gas diffusion layer, a function can be given by clamping a membrane hollowed out into a frame shape, etc. Alternatively, the electrolyte membrane is cut into a desired size in a state where there is no gas diffusion layer on the surface where the first catalyst layer is formed, and further joined to a frame-shaped membrane material and a gas diffusion layer, thereby making a single MEA. In addition, the gas diffusion layer can be laminated through a series of steps, wherein the catalyst solution for forming the first catalyst layer is applied to the electrolyte membrane, the gas diffusion layer is coated before drying, and the catalyst layer is passed through the gas diffusion layer to dry the catalyst layer.

[0131] [Third Embodiment: Production of Membrane-Electrode Assembly 3]

[0132] In the third embodiment, first, using Figure 4 The membrane-electrode assembly manufacturing apparatus 103 according to the embodiment shown forms a gas diffusion layer with a first catalyst layer on one surface of an electrolyte membrane. The formation of the gas diffusion layer with a first catalyst layer is carried out as follows.

[0133] In this embodiment, the electrolyte membrane 10' is supplied to the catalyst layer forming device 103 in a state supported on a support. The electrolyte membrane 10' with the support is unwound from the electrolyte membrane supply roll 11 and supplied to the thermocompression bonding section P. The electrolyte membrane 10' supplied to the thermocompression bonding section P is subjected to the same liquid imparting step and thermocompression bonding step as in the first embodiment, and the gas diffusion layer with the first catalyst layer is thermocompressed to form a membrane·first catalyst layer assembly 16'.

[0134] The membrane and gas diffusion layer assembly 16 ′ with the first catalyst layer is fed out by the feed roll 14 while being attached to the support, and is wound into a roll by the wind-up roll 17 .

[0135] Next, use Figure 5 The catalyst layer forming device 104 according to the embodiment shown forms the second catalyst layer on the back side of the electrolyte membrane on which the gas diffusion layer with the first catalyst layer is formed. The second catalyst layer is formed as follows.

[0136] The membrane and first catalyst layer assembly 16 ′ is unwound from the supply roll 18 , and the support 51 is peeled off from the interface with the electrolyte membrane via the guide rolls 26A and 26B. The peeled support 51 is wound around the support winding roll 50 .

[0137] The membrane and gas diffusion layer assembly 16 ′ with the first catalyst layer peeled off is subjected to the formation of the second catalyst layer by the catalyst solution coating mechanism 72 and the drying mechanism 74 similar to those of the third embodiment, thereby obtaining a membrane and electrode assembly 13 d .

[0138] The membrane-electrode assembly 13 d is fed out by a feed roll 14 , and is wound into a roll shape by a wind-up roll 15 .

[0139] In this state, there is no gas diffusion layer on the surface of the electrolyte membrane where the second catalyst layer is formed, but before further joining the gas diffusion layer, a function can be given by clamping the membrane hollowed out into a frame shape, etc. Alternatively, the electrolyte membrane can be cut into a desired size in a state where there is no gas diffusion layer on the surface of the electrolyte membrane where the second catalyst layer is formed, and further joined to a frame-shaped membrane material and a gas diffusion layer, thereby making a single MEA.

[0140] Example

[0141] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.

[0142] In Examples 1 to 6, the gas diffusion layer with a catalyst layer used the following gas diffusion layer roll, that is, a catalyst coating liquid formed by a Pt-supported carbon catalyst TEC10E50E manufactured by Tanaka Precious Metals Industries, Ltd. and a "Nafion" (registered trademark) solution was coated on a gas diffusion layer 28BC manufactured by SGL Corporation as a substrate, and then dried, and the produced gas diffusion layer with a catalyst layer was made into a rolled gas diffusion layer roll with a catalyst layer (substrate width 100 mm, thickness 240 μm) (platinum loading: 0.3 mg / cm 2 ).

[0143] In addition, the production of the electrolyte membranes in Examples 2 to 6 was carried out with reference to the production method described in Japanese Patent Application Publication No. 2018-60789.

[0144] [Example 1]

[0145] use Figure 1 The device having the schematic structure shown is a device in which the catalyst layer of the gas diffusion layer with a catalyst layer is joined to one surface of a commercially available "Nafion" (registered trademark) membrane, trade name NR211 (membrane thickness 25 μm), used as an electrolyte membrane, in accordance with the method described in the first embodiment described above.

[0146] In the liquid application step, a fan-shaped spray nozzle CBIMV 80005S manufactured by IKEUCHI CO., LTD. was used to spray 100% pure water at a rate of 1 cm 2 An amount of 0.4 μL was applied to the catalyst layer in the form of drops.

[0147] In the hot pressing process, a pair of hot pressing rollers with a diameter of 250 mm was used, one of which was a stainless steel roller and the other was a fluororubber roller with a hardness of 90° (Shore A). In addition, the pressure of the hot pressing roller was set to 3.0 MPa. It should be noted that the pressure is a measured value using a pressure measuring sheet made by Fuji Film Co., Ltd. The roller surface temperature was set to 160°C, and the heating temperature was measured by a thermocouple set at the bonding interface, and the result was 115°C. The conveying speed of the electrolyte membrane and the gas diffusion layer with a catalyst layer was 4.0 m / min.

[0148] The obtained membrane-electrode assembly was visually evaluated. As a result, the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0149] [Example 2]

[0150] use Figure 1 The device of the schematic structure shown in the figure is characterized by joining a catalyst layer of a gas diffusion layer with a catalyst layer identical to the layer used in the aforementioned Example 1 to one side of a polyether ketone-based polymer electrolyte membrane formed by a polymer represented by the following formula (G1).

[0151] [Chemical formula 1]

[0152]

[0153] In the liquid application step, a fan-shaped spray nozzle CBIMV 80005S manufactured by IKEUCHI CO., LTD. was used to spray 100% pure water at a rate of 1 cm 2 An amount of 0.4 μL was applied to the catalyst layer.

[0154] In the hot pressing process, a pair of hot pressing rollers with a diameter of 250 mm was used, one of which was a stainless steel roller and the other was a fluororubber roller with a hardness of 90° (Shore A). In addition, the pressure of the hot pressing roller was set to 4.8 MPa. It should be noted that the pressure is a measured value using a pressure measuring sheet made by Fuji Film Co., Ltd. The temperature of the roller surface was set to 160°C, and the heating temperature was measured by a thermocouple set at the bonding interface, and the result was 115°C. The conveying speed of the electrolyte membrane and the gas diffusion layer with a catalyst layer was 4.0 m / min.

[0155] The obtained membrane-electrode assembly was visually evaluated. As a result, the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0156] [Example 3]

[0157] use Figure 1 The device having the schematic structure shown in the figure is configured in accordance with the method described in the first embodiment described above, wherein the catalyst layer of the gas diffusion layer with a catalyst layer is joined to one surface of a polyarylene-based polymer electrolyte membrane formed of a polymer represented by the following formula (G2).

[0158] [Chemical formula 2]

[0159]

[0160] (In formula (G2), k, m and n are integers, k is 25, m is 380, and n is 8.)

[0161] The liquid applying step and the thermocompression bonding step were performed in the same manner as in Example 2.

[0162] The obtained membrane-electrode assembly was visually evaluated. As a result, the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0163] [Example 4]

[0164] use Figure 1 The device of the schematic structure shown in the figure is, according to the method described in the aforementioned first embodiment, a catalyst layer of the gas diffusion layer with a catalyst layer is joined to one side of a polyethersulfone-based polymer electrolyte membrane formed by a segment represented by the following formula (G3) and a segment represented by the following formula (G4).

[0165] [Chemical formula 3]

[0166]

[0167] (In formulas (G3) and (G4), p, q, and r are integers, p is 170, q is 380, and r is 4.)

[0168] The liquid applying step and the thermocompression bonding step were performed in the same manner as in Example 2.

[0169] The obtained membrane-electrode assembly was visually evaluated. As a result, the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0170] [Example 5]

[0171] According to the method described in the second embodiment, a membrane-electrode assembly is produced.

[0172] use Figure 2 The device of the schematic structure shown in the figure is coated with a catalyst solution on one side of a polyetherketone polymer electrolyte membrane formed by a polymer represented by the above formula (G1), and dried to form a first catalyst layer. The catalyst solution is a catalyst coating liquid formed by a Pt-supported carbon catalyst TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. and a "Nafion" (registered trademark) solution. The catalyst layer is dried at 120°C for 5 minutes to obtain a catalyst layer with a layer thickness of 5 μm.

[0173] Next, use Figure 3 The device with the schematic structure shown in the figure, regarding the gas diffusion layer with the second catalyst layer, the catalyst layer of the gas diffusion layer with the catalyst layer is bonded to the other side of the polyetherketone polymer electrolyte membrane with the first catalyst layer, so as to form the gas diffusion layer with the second catalyst layer. The cover film laminated on the first catalyst layer surface uses the PET film "Lumirror" (registered trademark) with a film thickness of 75 μm manufactured by Toray Industries, Ltd. The liquid application process and the thermal compression bonding process use the same method as in Example 2.

[0174] The covering film was peeled off from the obtained membrane·electrode assembly, and no attachments were observed on the covering film. In addition, the obtained membrane·electrode assembly was visually evaluated, and the results showed that the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0175] [Example 6]

[0176] According to the method described in the third embodiment, a membrane-electrode assembly is produced.

[0177] use Figure 4 The device with the schematic structure shown above joins the first catalyst layer from the aforementioned gas diffusion layer with a catalyst layer to one side of a polyetherketone polymer electrolyte membrane formed of a polymer represented by the above formula (G1). The liquid application step and the thermal compression step are the same as those in Example 2.

[0178] Next, use Figure 5 In the device having the schematic structure shown, the catalyst solution similar to that of Example 5 is applied to the other side of the electrolyte membrane on which the gas diffusion layer with the first catalyst layer is formed, and dried to form the second catalyst layer.

[0179] The obtained membrane-electrode assembly was visually evaluated. As a result, the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, indicating that the assembly was of high quality.

[0180] [Example 7]

[0181] A membrane-electrode assembly was produced in the same manner as in Example 1 except that the following composite electrolyte membrane was used as the electrolyte membrane. The obtained membrane-electrode assembly was visually evaluated and found to be of high quality with no damage to the gas diffusion layer with the catalyst layer, swelling or wrinkling of the electrolyte membrane.

[0182] <Composite electrolyte membrane>

[0183] A composite electrolyte membrane was prepared by impregnating a 6 μm-thick PTFE porous substrate ("Tetratex", a registered trademark, manufactured by Donaldson) with the following fluorine-based electrolyte solution.

[0184] <Fluorine-based electrolyte solution>

[0185] 80 parts by mass of ethylene glycol were added to 100 parts by mass of a 20% "Nafion (registered trademark)" n-propanol solution, and the n-propanol was removed under reduced pressure to perform solvent replacement, thereby obtaining an ethylene glycol solution of "Nafion".

[0186] [Example 8]

[0187] A membrane-electrode assembly was produced in the same manner as in Example 5 except that the following composite electrolyte membrane was used as the electrolyte membrane. The obtained membrane-electrode assembly was visually evaluated and found to be of high quality with no damage to the gas diffusion layer with the catalyst layer, swelling or wrinkling of the electrolyte membrane.

[0188] <Composite electrolyte membrane>

[0189] A composite electrolyte membrane was prepared by impregnating a 6 μm-thick PTFE porous substrate ("Tetratex" registered trademark, manufactured by Donaldson) with the following hydrocarbon-based electrolyte solution.

[0190] <Hydrocarbon-based electrolyte solution>

[0191] The preparation is carried out by dissolving 0.26 parts by mass of a nonionic fluorine-based surfactant (polyoxyethylene ether-based surfactant "Ftergent" (registered trademark) FTX-218 manufactured by NEO Co., Ltd.) in 100 parts by mass of an N-methylpyrrolidone (NMP) solution (electrolyte concentration: 13% by mass) in which the polyether ketone-based polymer electrolyte represented by the above formula (G1) is dissolved.

[0192] [Example 9]

[0193] exist Figure 1 In the manufacturing apparatus of , the nozzle chambers 32A and 32B were not depressurized, and a membrane-electrode assembly was manufactured in the same manner as in Example 1. The obtained membrane-electrode assembly was visually evaluated, and the result showed that the gas diffusion layer with the catalyst layer was not damaged, and the electrolyte membrane was not swollen or wrinkled, and was of high quality.

[0194] [Comparative Example 1]

[0195] The same operation as in Example 2 was carried out except that the liquid imparting step was not carried out, and the catalyst layer was joined to one side of the electrolyte membrane from the gas diffusion layer with the catalyst layer which was the same as the layer used in the aforementioned Example 1. The obtained membrane-electrode assembly was visually evaluated, and as a result, poor adhesion between the electrolyte membrane and the catalyst layer was observed.

[0196] Industrial Applicability

[0197] The membrane-electrode assembly of the present invention can be suitably used in, for example, a polymer electrolyte fuel cell, a polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, and the like.

[0198] Description of Reference Numerals

[0199] 100, 102, 103: Membrane-electrode assembly manufacturing apparatus

[0200] 101, 104: Catalyst layer forming device

[0201] 10, 10': Electrolyte membrane

[0202] 11, 18: Electrolyte membrane supply roller

[0203] 13a, 13b, 13c, 13d: membrane-electrode assembly

[0204] 14: Delivery roller

[0205] 15, 17: Winding roller

[0206] 16: Membrane and first catalyst layer assembly

[0207] 16': Membrane and gas diffusion layer assembly with first catalyst layer

[0208] 12, 22A, 22B, 26A, 26B, 27A, 27B: guide rollers

[0209] 20A, 20B: Gas diffusion layer with catalyst layer

[0210] 21A, 21B: Gas diffusion layer supply roller with catalyst layer

[0211] 30A, 30B: Spray nozzle

[0212] 31A, 31B, 73: Support rollers

[0213] 32A, 32B: Nozzle chamber

[0214] 33A, 33B: valve

[0215] 34A, 34B: Pressure reducing tank

[0216] 40A, 40B: Hot pressing roller

[0217] 41A, 41B: Heat insulation board

[0218] 50: Support winding roller

[0219] 51: Support body

[0220] 60: Cover film supply roller

[0221] 70: Catalyst solution tank

[0222] 71: Catalyst solution delivery pump

[0223] 72: Coating mechanism

[0224] 74: Drying mechanism

[0225] P: Thermocompression bonding

[0226] S: Space

Claims

1. A method for producing a membrane-electrode assembly, wherein a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane, the method comprising: a liquid applying step of applying the liquid only to the surface of the catalyst layer before joining in an air atmosphere; and, Thermocompression bonding process is to bond the gas diffusion layer with the catalyst layer to which the liquid has been applied and the electrolyte membrane by thermocompression bonding. The liquid applied in the liquid applying step is a liquid containing 90% by mass to 100% by mass of water. The liquid applying step and the thermocompression bonding step are performed while the electrolyte membrane and the gas diffusion layer with the catalyst layer are conveyed separately.

2. The method for producing a membrane-electrode assembly according to claim 1, wherein: In the thermocompression bonding step, the gas diffusion layer with the catalyst layer to which the liquid is applied and the electrolyte membrane are brought into contact with each other and are bonded together by thermocompression bonding.

3. The method for producing a membrane-electrode assembly according to claim 1 or 2, wherein: The thermal compression bonding step includes a step of passing the electrolyte membrane and the gas diffusion layer with the catalyst layer between a pair of thermal compression rollers, one of which is made of metal and the other of which is a roller having an elastic body coated on its surface.

4. The method for producing a membrane-electrode assembly according to claim 1 or 2, wherein: In the liquid applying step, the liquid is applied in the form of droplets onto the catalyst layer surface of the gas diffusion layer with the catalyst layer.

5. The method for producing a membrane-electrode assembly according to claim 4, wherein: In the liquid applying step, the liquid is applied using a sprayer.

6. The method for producing a membrane-electrode assembly according to claim 1 or 2, wherein: In the liquid applying step, the amount of the liquid in the thermal compression bonding step is relative to 1 cm 2 The surface of the catalyst layer is greater than 0.1 μL and less than 5 μL.

7. The method for producing a membrane-electrode assembly according to claim 1 or 2, wherein: As the electrolyte membrane, a hydrocarbon-based electrolyte membrane is used.

8. A method for producing a membrane-electrode assembly, comprising the following steps: A step of applying a catalyst solution on one side of an electrolyte membrane and drying the solution to form a first catalyst layer; and, A step of forming a second catalyst layer by bonding a gas diffusion layer with a catalyst layer to the other surface of the electrolyte membrane using the method according to any one of claims 1 to 7.

9. The method for producing a membrane-electrode assembly according to claim 8, further comprising the step of covering the first catalyst layer with a covering film, and forming the second catalyst layer in a state where the first catalyst layer is covered with the covering film.

10. A method for producing a membrane-electrode assembly, comprising the following steps: A step of applying a catalyst solution on one side of the electrolyte membrane to form a first catalyst layer; A step of coating the first catalyst layer with a gas diffusion layer before drying; a step of drying the catalyst layer by passing through the gas diffusion layer; and A step of forming a second catalyst layer by bonding a gas diffusion layer with a catalyst layer to the other surface of the electrolyte membrane using the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Membrane-electrode assembly manufacturing method

    JP2009140652A

  • Manufacturing method of membrane electrode assembly for polymer electrolyte fuel cell

    JP2013069535A

  • Polymer electrolyte composition and polymer electrolyte membrane prepared therewith, electrolyte membrane with catalyst layer, membrane electrode complex, solid polymer fuel cell, electrochemical hydrogen pump and water-electrolytic hydrogen generating device

    JP2018060789A

  • Manufacturing method of junction of electrolyte membrane and electrode

    JP2005158518A

  • Method and device for manufacturing membrane-catalyst layer assembly

    JP2017068898A